2012
DOI: 10.1111/j.1740-8261.2011.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature and Age on the T1 Relaxation Time of the Equine Distal Limb

Abstract: The extent of fat suppression using short tau inversion recovery (STIR) imaging is variable between horses. Our aim was to determine if patient's age and/or hoof temperature have an influence on the T(1) relaxation time of bone marrow in the equine distal limb, thereby affecting the suppression of fat signal. Magnetic resonance imaging was conducted on standing horses and cadaver samples using a low-field magnet (0.27 T). The hoof temperature was measured at the lateral side of the coronary band. A modified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Besides motion artifacts, other factors may contribute to suboptimal image quality in inversion recovery sequences, namely choice of an improper inversion time relative to the temperature of the limb or to the age of the horse may lead to deficient fat signal suppression. 16 In the study reported here, such horses with increased SI on STIR images but no manifestation of phase-cancellation artifact on T2*-weighted images were allocated to the no-BML group. However, it remains possible that data from horses with abnormal SI on T1-weighted and T2*-weighted images and increased SI in the fatsuppressed images due to a combination of a BML and lack of fat saturation might have altered the results by artificially increasing the measured SNR and CNR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides motion artifacts, other factors may contribute to suboptimal image quality in inversion recovery sequences, namely choice of an improper inversion time relative to the temperature of the limb or to the age of the horse may lead to deficient fat signal suppression. 16 In the study reported here, such horses with increased SI on STIR images but no manifestation of phase-cancellation artifact on T2*-weighted images were allocated to the no-BML group. However, it remains possible that data from horses with abnormal SI on T1-weighted and T2*-weighted images and increased SI in the fatsuppressed images due to a combination of a BML and lack of fat saturation might have altered the results by artificially increasing the measured SNR and CNR.…”
Section: Discussionmentioning
confidence: 98%
“…The manufacturer also proposes 2 additional versions of the STIR sequence with shorter and longer TI (named STIR + and STIR -, respectively) to increase fat suppression depending on limb temperature and age-related maturity of fat. 16 Only cases evaluated with standard STIR (constant TI, 85 milliseconds) images of diagnostic quality were included in this report for consistency, and cases with obvious fat suppression deficiency for any reason were excluded. There was probably less trabecular fat T1 relaxation time variation in our group of horses mainly composed of adult Warmbloods scanned in temperate zones, compared with young Thoroughbreds or horses scanned in tropical or polar zones.…”
Section: Discussionmentioning
confidence: 99%
“…• Short-Tau-Inversion-Recovery-Sequenz (STIR): sagittal Die Time of Repetition (TR) der STIR-Sequenzen, die zu einer optimalen Fettunterdrückung führte, wurde mithilfe eines sogenann-ten STIR-Tests bestimmt (1). Bei einigen Patienten wurden weitere Ebenen der angegebenen Sequenzen untersucht, teilweise auch zusätzliche, nicht aufgeführte Sequenzen.…”
Section: Materials Und Methodenunclassified
“…Scans included sagittally‐aligned T1‐weighted (W) gradient echo (GRE), T2*W‐GRE, T2W fast spin echo (FSE) and short tau inversion recovery (STIR) FSE sequences and a dorsally aligned T1W‐GRE sequence (http://onlinelibrary.wiley.com/doi/10.1111/evj.12370/suppinfo). The STIR‐FSE sequence used had a relatively short inversion time following recommendations for tissue scanning at temperatures between refrigeration and room temperature . Images were transferred to a work station with DICOM viewing software (OsiriX v 4.1.2) d for evaluation.…”
Section: Methodsmentioning
confidence: 99%